PERNIKAHAN DINI SEBAGAI PENCEGAHAN ZINA DAN PENDEWASAAN REMAJA DALAM PERSPEKTIF KITAB ADABUL ISLAM FII NIDZHOMIL USROH - Mushthafa Hilmiy Ar-Rasyiid Zako (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2023)
Many Indonesian people are poisoned by adultery today. Many test results show that many girls or young women in Indonesia have lost their virginity, and we also see many cases of pregnancy out of wedlock. The existence of this research tries to find a way out of the source of this problem. The research method used here is a qualitative research method of the type of library research which is carried out by looking for references from various sources of books on Islamic law and especially from the coral book of Prof. Dr. As-Sayyid Muhammad bin Alwi al-Maliki al-Hasani who is often called Abuya Maliki. The results of the research found several of them: first, Abuya Maliki composed this book because of the sad problems that occur in marriage and especially the problems of the Muslim household. Second, Abuya Maliki wrote this book in an orderly manner that is easy to understand and describes one by one the problems that are rife and then explains the way out of them all. Third, that the problem raised by the researcher existed from the time Abuya Maliki composed the book, and now it has become more than just a tumor that attacks a person's body.